2009
DOI: 10.1186/1471-2164-10-385
|View full text |Cite
|
Sign up to set email alerts
|

Microbial comparative pan-genomics using binomial mixture models

Abstract: BackgroundThe size of the core- and pan-genome of bacterial species is a topic of increasing interest due to the growing number of sequenced prokaryote genomes, many from the same species. Attempts to estimate these quantities have been made, using regression methods or mixture models. We extend the latter approach by using statistical ideas developed for capture-recapture problems in ecology and epidemiology.ResultsWe estimate core- and pan-genome sizes for 16 different bacterial species. The results reveal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 19 publications
3
120
0
1
Order By: Relevance
“…Desiccation is a common and unique environmental stress in soil, and soil-dwelling bacteria are generally equipped with mechanisms for desiccation resistance (33,41). Since habitat stresses affect bacterial adaptation and divergence within the same species (35,39), one may expect that the E. coli strains that inhabit soil generally exhibit higher desiccation resistance than strains occupying other niches. The present study showed that four soil E. coli strains survived better than the common lab strain MG1655 in desiccated sterile quartz sand.…”
Section: Discussionmentioning
confidence: 99%
“…Desiccation is a common and unique environmental stress in soil, and soil-dwelling bacteria are generally equipped with mechanisms for desiccation resistance (33,41). Since habitat stresses affect bacterial adaptation and divergence within the same species (35,39), one may expect that the E. coli strains that inhabit soil generally exhibit higher desiccation resistance than strains occupying other niches. The present study showed that four soil E. coli strains survived better than the common lab strain MG1655 in desiccated sterile quartz sand.…”
Section: Discussionmentioning
confidence: 99%
“…GET_HOMOLOGUES defines these compartments empirically, as follows: core, genes contained in all genomes/taxa considered; soft core, genes contained in 95% of the genomes/taxa considered, as in the work of Kaas and collaborators (25); cloud, genes present only in a few genomes/taxa (the cutoff was defined as the most populated noncore cluster class and its immediately neighboring classes); shell, the remaining genes, present in several genomes/taxa. This script will also compute estimates of core and pangenome sizes under the binomial mixture model of Snipen and colleagues (26). If the source genomic data are provided in GenBank format, parse_pangenome_matrix.pl can be asked to plot the clade-specific genes on a linearized genetic map of a reference genome selected from that lineage.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the 22 complete genome sequences of E. coli that are currently available, the E. coli pangenome (the complete complement of noncore genes distributed within individuals within the species) has been estimated to comprise at least 42,500 gene families (51), significantly more than the human genome. Studies have revealed enormous diversity in E. coli populations in primary and various secondary habitats.…”
Section: Vol 76 2010 Distribution and Diversity Of E Coli In A Watmentioning
confidence: 99%